PROTECTIVE EFFECT OF NQO-1 MODULATOR QUERCETIN IN HYPERTENSIVE RATS (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Despite abundant anti-hypertensive therapies, there always remains an opportunity (perhaps need) to identify novel targets. One such emerging target is NAD(P)H:quinone oxidoreductase 1 (NQO-1), which acts downstream in Nrf2 cascade. This study was planned to investigate the effect of Nrf2 activator quercetin on NQO-1 modulation in hypertensive wistar albino rats. The hypertension was induced by DOCA (25 mg/kg s.c. twice weekly) and 1% NaCl in drinking water. The animals were randomized into six groups receiving either vehicle (control), DOCA- 1% NaCl salt (model) or treatments (Telmisartan (10 mg/kg) and quercetin (10, 25, 50 mg/kg) for 5 weeks. Various haemodynamic parameters, left ventricular functions, biological markers, lipid and protein peroxidative marker, antioxidant enzymes activity as well as histology (heart and kidney) were carried out. The expression of mRNA of NQO-1 gene in heart homogenate was estimated. Treatment with quercetin significantly prevented the rise in blood pressure, organ weight, improved left ventricular function, cardiac markers profile, kidney markers, restored antioxidant enzymes along with decrease in lipid and protein peroxidation. The normal architecture of heart and kidney were preserved in histopathological analysis by quercetin treatment. The upregulation of NQO-1 gene in heart by quercetin resulted in normal blood pressure. Altogether, quercetin prevented hypertension, improved cardiac function by augmenting the innate cell defense system in DOCA-salt rats. Such promising effects are attributed to novel cellular level target, NQO-1, which have multiple effects like regularisation of oxidative stress, eNOS activation and inhibition of ACE shedding.